2009
DOI: 10.1021/jf9026348
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Activity of New (E)-α-(Methoxyimino)benzeneacetate Derivatives Containing a Substituted Pyrazole Ring

Abstract: Strobilurins are one of the most important classes of agricultural fungicides. To discover new strobilurin analogues with high activity, a series of new strobilurin derivatives containing a substituted pyrazole in the side chain were synthesized and their biological activities were tested. The compounds were identified by (1)H nuclear magnetic resonance, infrared, and elemental analysis. The test results indicated that the compounds exhibited strong fungicidal activities against Pyricularia oryzae , Phytophtho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 14 publications
3
38
0
Order By: Relevance
“…Here, we prepared the 2-methylated b-ketoesters observing no issues regarding dialkylation. Our protocol avoids the use of strong bases and acylating reagents and leads to both, yields and scope, comparable or even better than those reported in literature [27,29,32,33,[55][56][57][58][59][60]. This was clearly shown for compound 3b, where different methodologies and their respective yields are presented (Scheme 6) [27,29,33,[55][56][57].…”
Section: Resultssupporting
confidence: 73%
“…Here, we prepared the 2-methylated b-ketoesters observing no issues regarding dialkylation. Our protocol avoids the use of strong bases and acylating reagents and leads to both, yields and scope, comparable or even better than those reported in literature [27,29,32,33,[55][56][57][58][59][60]. This was clearly shown for compound 3b, where different methodologies and their respective yields are presented (Scheme 6) [27,29,33,[55][56][57].…”
Section: Resultssupporting
confidence: 73%
“…The purification procedure of compounds 9-25 was recrystallization from isopropanol, the residue was purified through column chromatography using petroleum ether and ether as eluent to get products 1-8, 26 [34]. (5 Amino-3-(methylthio)-1-(2,4,6-trichlorophenyl) (9) (10 (11 (12 (14). Yield, 96%; white solid; m.p.…”
Section: General Procedures For the Preparation Of Compounds 1-26mentioning
confidence: 99%
“…Compounds with pyrazole functional units exhibit antimicrobial [7], herbicidal [8], antitumor [9], insecticidal [10][11][12][13], fungicidal [14][15][16][17][18] and antiviral activities [19,20]. Lamberth [21] has summarized the significance of pyrazole derivatives in crop protection chemistry, including herbicidally-, fungicidally-and insecticidally-active pyrazole classes.…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25][26] Utilizing the intermediate derivatisation method based on the active substructure combination and bioisosteric replacement, 27 a series of novel strobilurin derivatives containing pyrimidine moieties and strobilurin pharmacophore were designed and synthesized with the aim of obtaining more active candidates than the conventional azoxystrobin, hopefully against resistant fungal strains. The bioassays showed that most of the β-methoxyacrylate analogues exhibited potential antifungal activities against Colletotrichum orbiculare, Botrytis cinerea Pers and Phytophthora capsici Leonian.…”
Section: 13mentioning
confidence: 99%